Aesthetic Reconfigurations of the Political during the Pandemic: Group Representations in Covid-19 Special Programmes on German Public Television - Christiane Barnickel; Dorothea Horst (CADAAD Journal, 2024)
We analyse audiovisual media discourse on Covid-19 through the lens of the politicalin order to illustrate how discursive practices establish and reconfigure subject positionsand social orders in times of crisis. Drawing on Jacques Rancière's understanding of thepolitical, we suggest that these reconfigurations can either stabilise existing (political)communities and power relations, or intervene in what is perceived as `normal'.Analytically, we approach these (re)configurations on the level of media-aesthetics (thetangible), language (the utterable) and audiovisual representation (the visible) todemonstrate how a sense of commonality is produced or revised through artistic mediapractice (Richard Rorty).We demonstrate our argument by means of Covid-19 `special programmes' onGerman public television, as they can be considered cultural practices of making situatedsense of a global crisis. By analysing the tangible, the utterable and the visible in thebroadcast from 13 December 2020, our illustrative analysis reveals a constant strugglebetween reconfigurations of the political and stabilisations of (a new) normalcy. Weconclude with a plea for including a media-aesthetic perspective into the analysis of Covid19 discourse as it opens up a more comprehensive (multimodal) idea and experientialdimension of the discursive construction of the pandemic.
Keywords: 320; the political; media aesthetics; Covid-19 discourse; audiovisual data; Germany